QUALITY EDUCATION: THE KEY ROLE OF TEACHERS - Dr. Precious Sheron and Ms. Navninder Kaur (International journal of economic perspectives, 2022)
The World Education Forum in Dakar in 2000 did not only emphasize the need to achieve education for all, but also noticed the need to improve the quality of education. The Forum made the following recommendation: “Improve all aspects of the quality of education to achieve recognized and measurable learning outcomes for all- especially in literacy, numeracy and essential life skills”(Dakar Framework for Action. Article 7, World Education Forum,2000). Aricle 28 of convention on the Rights of the child states the child’s right to education and the state’s duly to ensure that primary education at least is made free. In Article 29 of the same Convention, the states are requested to recognize that education should be directed at developing the child’s personality and talents, preparing the child for active life as an adult, fostering respect for basic human rights and developing respect for the child’s own cultural and national values and those of others (United Nations,1989).